Structural Investigations in Electrochromic Vanadium Pentoxide Thin Films. Issue 16 (19th October 2021) - Romanitan, Cosmin; Tudose, Ioan Valentin; Mouratis, Kyriakos; Popescu, Marian Catalin; Pachiu, Cristina; Couris, Stelios; Koudoumas, Emmanouel; Suchea, Mirela
Abstract : Herein, the correlation between the texture coefficient and the electrochromism in vanadium pentoxide nanostructured films with orthorhombic symmetry obtained by spray pyrolysis technique is reported. From a microstructural point of view, X‐ray diffraction depicts that the size of the crystalline domains, evaluated from both Scherrer equation and Rietveld refinement, depends on the texture coefficient, which further implies that the dislocation density is related to the texture coefficient. From the applications point of view, a high texture coefficient is found to facilitate the insertion of charge, thus reaching a density of −73.30 and 70.76 mC cm −2 on coloration and bleaching, respectively. On the contrary, a small texture coefficient can provide an inserted charge density of only −4.38 and 3.79 mC cm −2 on coloration and bleaching. Moreover, a higher texture coefficient induces a higher transmittance contrast under an applied voltage of ±1 V, reaching 18.48% for the most textured sample. It is clear that the texture parameter is a key factor in the context of both microstructural parameters and electrochromic performances. Abstract : Herein, the correlation between the texture coefficient and the color change ability for orthorhombic α‐V2 O5 in the range of ±1 V is established. More specifically, it is shown that the inserted charge storage and the optical transmittance are favored by an increase in the texture coefficient along the [001] direction, which reflects a "more regular" arrangement of the atomic planes.